Effect of boswellia (Boswellia serrata L.) supplementation on glycemic markers and lipid profile in type 2 diabetic patients: a systematic review and meta-analysis - Karimi, Mehdi; Vakili, Kimia; Rashidian, Pegah; Razavi-Amoli, Seyedeh-Kiana; Akhbari, Matin; Kazemi, Kimia (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundType 2 diabetes mellitus (T2DM) is a significant global health challenge whose prevalence is projected to increase alarmingly. Recently, due to better safety and fewer adverse effects, herbal medicines have been used to manage T2DM. This study aimed to evaluate the efficacy of boswellia in improving glycemic markers and lipid profiles in T2DM patients.MethodsA comprehensive search was conducted on the PubMed, Web of Science, and Scopus databases for all relevant studies published up to April 30, 2024. The effects of boswellia supplementation were evaluated using glycemic markers and lipid profiles. The data were extracted and meta-analyzed using Stata software.ResultsThis meta-analysis included five studies with a total of 287 patients with T2DM. It was found that boswellia in patients with T2DM compared to the placebo or control group significantly reduced hemoglobin A1C (HbA1C) (SMD: -1.01; 95%CI: -1.55 to -0.46; P=0.00), total cholesterol (TC) (SMD: -0.44; 95%CI: -0.68 to -0.21; P=0.00), Triglycerides (TG) (SMD: -0.42; 95%CI: -0.66 to -0.19); P=0.00) and low-density lipoprotein (LDL) (SMD: -0.43; 95%CI: -0.73 to -0.12); P=0.006) levels, while reduced fasting blood glucose (FBG) but it was not significant (SMD: -1.34, 95%CI: -2.68 to 0.00; P=0.05). Notably, it did not affect high-density lipoprotein (HDL) (SMD: 0.56, 95%CI: -0.14 to -1.26; P=0.118).ConclusionIn summary, boswellia supplementation has the potential to improve glycemic markers and lipid profiles in patients with T2DM. It may help diabetic patients in addition to a controlled diet and other treatments.Systematic review registrationcrd.york.ac.uk/PROSPERO/display_record.php?RecordID=538347, identifier CRD42024538347.